Mengungkap Framing Media Massa: Pemberitaan Konser Coldplay 2023 oleh Kompas.com dan Konstruksi Realitas - Sesdia angela; Ceriah Dolis (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
Abstract The mass media has a profound influence on society's social perceptions. A case study conducted on online media Kompas.com about the Coldplay concert in Indonesia in 2023 is used in this article to study the role of the media in constructing social reality. The concert was a big hit and triggered a variety of reactions in the community. The aim of this study is to look at how the media broadcast this event, and how it affects public understanding and perception. This research uses Robert Entman's framing analysis. The framing analysis dimensions used are news responses, news assumptions, news principles, and news assessments. The data used for this analysis are articles published by Kompas.com during the Coldplay concert reporting period in Indonesia. Robert Entman's model framing theory is used as a framework for analysis. This theory helps us understand how the mass media chooses a particular viewpoint to report an event and how it can influence public understanding and interpretation of the event. The analysis shows that Kompas.com used framing that drew the attention of Coldplay fans who were very enthusiastic during their concerts in Indonesia. This media increases public understanding by linking these events to environmental issues, especially the problem of garbage. The results show that the mass media plays an important role in shaping the public's perspective on popular cultural events and relevant social issues. Keywords: mass media, popular culture, framing analysis, Robert Entman